A Festa do patrimônio intercultural: patrimonialização e transformações das festividades do Glorioso São Sebastião nos Marajós - GOMES, Layane Rayssa Gaia (2019)
This research addresses the festivities of Glorioso São Sebastião, which occur in 14 municipalities in Marajó's middle region, which were inserted in Iphan Celebrations Book at 2013, constituting as a process of recognized and safeguard Intangiblen Heritage Brazilian as well. It is an exploratory and descriptive research, based on techniques for collecting qualitative data, which aims to identify the changes occurred in the festivities starting from their record. For this, fieldwork was carried out at January 2016 during the festivities in two municipalities representing different Marajós: São Sebastião da Boa Vista, located at Marajó Forest, and Cachoeira do Arari, situated in Marajó Field. The focus of the research was listening to the possessors of the festivities, their joys and difficulties at arrange and develop these events, to later analyze the registration process and State's planning for safeguarding. In this sense, presents the safeguarding actions of the festivities already in place, highlighting the role of Iphan in safeguarding the intangible heritage. Also analyzes how the record and safeguard actions changed the symbols and practices developed in the festivities. As a result, there were different levels of knowledge and exploitation about public policy of the heritage protection by their owners. As well, the different configurations and symbologies that the festivities take, constituting as an intercultural heritage.